Health insurance ownership among female workers in Indonesia: does socioeconomic status matter? - Agung Dwi Laksono; Wahyu Pudji Nugraheni; Nikmatur Rohmah; Ratna Dwi Wulandari (BMC, 2022)
Abstract Background Female workers are vulnerable groups in the Indonesian context, and female workers must be responsible for domestic problems and earn a living. The study aimed to analyze the role of socioeconomic on health insurance ownership among female workers in Indonesia. Methods The study population was all female workers in Indonesia. This cross-sectional study involved 7,943 respondents. The study analyzed health insurance ownership as an outcome variable and socioeconomic status as an exposure variable. The study also involved five control variables: residence, age, marital, education, and occupation. The research used multinomial logistic regression in the final step. Results The results show the poorest female workers have a possibility of 0.735 times more than the richest to have NHI (AOR 0.733; 95% CI 0.733-0.737). The poorer female workers have 0.939 times less likely than the richest to have NHI (AOR 0.939; 95% CI 0.937-0.942). Female workers with middle socioeconomic status are possibly 0.833 times less than the richest to have NHI (AOR 0.833; 95% 0.831-0.835). Moreover, the richer female workers have 1.028 times more likely than the richest to have NHI (AOR 1.028; 95% CI 1.025-1.030). Moreover, all socioeconomic statuses have a lower possibility than the richest of having other health insurance. Conclusions The study concluded that socioeconomic has a role in health insurance ownership among female workers in Indonesia.